Influence of Age and Palm Surface Area on Secondary Task Performance in a Driving Simulator - FUCHS, Lukas; NARASINGHE, Netmi; SCHMID, Peter; MAIER, Thomas (Promet - Traffic&Transportation, 2026)
Gesture control allows for reduced glance interaction compared to touchscreens when controlling secondary functions in cars. However, to date, there has been a lack of research investigating the influence of age and palm surface area (PSA) on performance during dual task applications, such as driving a car and using gestures with mid-air haptics feedback for controlling secondary functions. The following study investigates ways to introduce a characteristic feedback point on a virtual slider which differs from the adjacent points. This is either by changing the intensity or the distance to adjacent points. The time and the slider value set by the participant were saved. Participants gave ratings for each of the nine parameter sets by answering questions about the usability and the user experience questionnaire. The study consisted of two age groups: 30 younger participants with an average age of 31.0 years and 31 older participants with an average age of 63.0 years. Three of the older participants reported not feeling the mid-air haptics at all. Significant differences were found between the age groups in subjective and objective terms, and significant correlations for PSA and two subjective parameters. Further research will evaluate the findings in a more immersive static driving simulator.